Factores que influyen en las infecciones intrahospitalarias de los pacientes postquirúrgicos de cirugía de cadera en el hospital de especialidades Fuerzas Armadas n º 1 en el periodo octubre 2019 – marzo 2020 - Bosquez Auquilla, Viviana Yadira (2020)
According to the World Health Organization, hip fractures are considered as a new orthopedic epidemic that profoundly affects the physical, mental and functional balance of human beings, is usually related to the aging process and are all consequences derived of it, even more so if in the post-surgical procedures, the presence of in-hospital infections is noticed. The present study "Factors that influence in-hospital infections of post-surgical hip surgery patients at the Armed Forces Specialties Hospital No. 1 in the period October 2019 - March 2020" allowed to identify that there are intrinsic risk factors such as age over the 60 years; female sex, menopause;; cardiovascular diseases and diabetes; other extrinsic ones as breaking the rules of biosafety and nursing care that affect the appearance of hospital infections. In order to meet the stated objectives, the methods were considered: inductive, descriptive and historical, in the same way, observation guides were applied to the nursing staff, checklist to the history of post-surgical hip surgery patients and family surveys. and patients, to obtain as conclusions that 24% of the operated patients presented intrahospital infections related to the presence of Enterococcus faecalis, Candida Albicans, Coli blee and Pseudomona auroginosa, in addition the importance of implementing information and training strategies about Causes and consequences of in-hospital infections.